Effect of desloratadine and loratadine on rhinovirus-induced intercellular adhesion molecule 1 upregulation and promoter activation in respiratory epithelial cells - Papi, A.; Papadopoulos, N. G.; Stanciu, L. A.; Degitz, K.; Holgate, S. T.; Johnston, S. L. (J Allergy Clin Immunol, 2001)
Rhinoviruses have been recently associated with the majority of asthma exacerbations for which current therapy is inadequate. Intercellular adhesion molecule 1 (ICAM-1) has a central role in airway inflammation in asthma, and it is the receptor for 90% of rhinoviruses. Rhinovirus infection of airway epithelium induces ICAM-1. Desloratadine and loratadine are compounds belonging to the new class of H(1)-receptor blockers. Anti-inflammatory properties of antihistamines have been recently documented, although the underlying molecular mechanisms are not completely defined.|We have investigated the effects of desloratadine and loratadine on rhinovirus-induced ICAM-1 expression, mRNA upregulation, and promoter activation.|Cultured primary bronchial or transformed (A549) respiratory epithelial cells were pretreated with desloratadine and loratadine for 16 hours and infected with rhinovirus type 16 for 8 hours. ICAM-1 surface expression was evaluated with flow cytometry, and ICAM-1 mRNA was evaluated with specific RT-PCR. In A549 cells promoter activation was evaluated with a chloramphenicol acetyltransferase assay, and binding activity of nuclear factor kappa B in nuclear extracts was evaluated with an electrophoretic mobility shift assay.|Desloratadine and loratadine (0.1-10 micromol/L) inhibited rhinovirus-induced ICAM-1 upregulation in both primary bronchial or transformed (A549) respiratory epithelial cells. In A549 cells the 2 compounds showed a dose-dependent inhibition with similar efficacy (inhibitory concentration of 50%, 1 micromol/L). Desloratadine and loratadine also inhibited ICAM-1 mRNA induction caused by rhinovirus infection in a dose-dependent manner, and they completely inhibited rhinovirus-induced ICAM-1 promoter activation. Desloratadine also inhibited rhinovirus-induced nuclear factor kappa B activation. Desloratadine and loratadine had no direct effect on rhinovirus infectivity and replication in cultured epithelial cells.|These effects are unlikely to be mediated by H(1)-receptor antagonism and suggest a novel mechanism of action that may be important for the therapeutic control of virus-induced asthma exacerbations.
Keywords: Asthma Bronchi Epithelial Cells HeLa Cells Histamine H1 Antagonists Humans Intercellular Adhesion Molecule-1 Loratadine NF-kappa B Promoter Regions; Genetic Respiratory Mucosa Rhinovirus Transcriptional Activation Up-Regulation